The Construction of Diabetes Mellitus as a Health Threat in Local Media Reporting: A Framing Analysis of a BETV News Article - Martha Heriniazwi Dianthi; Dwi Aris Noprianto; Hazairi Hazairi (Utami Publisher, 2026)
Diabetes Mellitus is a non-communicable disease that continues to increase and has become a major public health concern, including at the local level. Beyond its biomedical dimension, diabetes is also a health communication issue, as public understanding of the disease is shaped by media coverage. This study aims to examine how Diabetes Mellitus is constructed as a health threat in local media reporting in Bengkulu. The study employs a qualitative approach using Robert M. Entman’s framing analysis to analyze a single news article published by BETV. Data were analyzed through four framing elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings indicate that Diabetes Mellitus is framed as an increasing health threat, particularly to younger generations, through the emphasis on numerical data and urgent language. The causes of diabetes are predominantly attributed to individual behaviors, such as excessive sugar consumption and unhealthy lifestyles, while structural factors receive limited attention. Moral judgments are implicitly conveyed by positioning individuals as primarily responsible for the disease, and proposed solutions focus on personal behavior change. This study highlights the role of local media in shaping health-related meanings and demonstrates the relevance of framing analysis in health communication research.